Exploring Affective Filter Levels in Spanish as a Foreign Language Course Among Tertiary Students - Dalilis, Daniela M.; Kiw-an, Farah Trisha M.; Siadto, Gelise E.; Pelila, John Rey O.; Bangkiko, Sharmaine May G. (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The affective filter hypothesis is critical to comprehending how emotions impact language learning, yet limited research exists on its correlation to other languages, specifically to Bachelor of Secondary Education (BSED) students studying Spanish as a foreign language. This study was to investigate the affective filter levels of BSED students from different majors and examine how their perceptions of classroom-related factors influence their language learning experiences. Using a quantitative, descriptive-comparative design and proportional stratified sampling, data were collected via an adapted version of Robert C. Gardner’s Attitude/Motivation Test Battery (AMTB), administered both online and in print. The results revealed that English and Values Education majors reported higher levels of affective filter, while Filipino majors exhibited lower levels, indicating that emotional barriers vary across different fields of specialization. Furthermore, there was strong agreement among students regarding the positive impact of classroom dynamics—such as teaching style, peer interaction, and the learning environment—on reducing emotional barriers and enhancing motivation. These findings emphasize the importance of teachers creating emotionally supportive learning environments that could help lower the affective filter and nurture better language learning outcomes. With these, further research involving more diverse student populations that focuses more on individual experiences and exploring additional foreign languages is recommended.